Microalgae strains Monoraphidium Griffithi and Chlorella sp. for the carbon dioxide capture from biogas - Juškaitė, Loreta; Zagorskis, Alvydas (International Conference “Environmental Engineering”, 2020)
One of the most important tools for mitigating climate change is biogas production. Increasing their use requires improving the energy value of biogas by reducing its carbon dioxide content while increasing the methane concentration in biogas. Biological purification of biogas using microalgae strains − merging biogas upgrading method where microalgae use carbon dioxide for their growth during the process of photosynthesis. A four-column photobioreactor was constructed with Monoraphidium Griffithi, Chlorella sp. microalgae strains, distilled water and MWH medium for purification of biogas. Experimental studies determined sizes, shapes and of microalgae cells, the pH changes of mediums used after biogas treatment and the composition of biogas before and after upgrading using photobioabsorber. Microalgae Monoraphidium Griffithi was estimated to have the greatest contribution to CO2 reduction by decreasing from 31.0% to 10.0%. The smallest reduction in CO2 was recorded when biogas was flowing through MWH medium. Experiments have shown that the absorption of biogas components results in the release of oxygen. As the biogas was flowing through all suspensions, the oxygen concentration increased from 3.6 to 5.2%.